Sensor capacitivo para imageamento direto de escoamentos bifásicos - Wrasse, Aluísio do Nascimento (2015)
Two-phase flow is present in many industrial applications, among them in petroleum industry as gas-liquid flow in pipelines. The knowledge of the phase distribution in the pipe flow is important for the efficiency and safety of the plants. In the academia, the knowledge of this phase distribution allows the understanding of physical phenomena, as well as gives support for the development, refinement and validation of physical models. In this work, a novel capacitive array sensor has been developed and its use was investigated to image two-phase flow. The measuring principle is based on the difference between electrical permittivity of the phases. Therefore the sensor can be applied to electrically non-conductive substances such as oil and organic liquids. Several simulations based on Finite Element Method have been performed to improve the sensor geometry and predict its electrical behavior. The sensor consists of two copper rings being one emitter and one receiver ring. Receiver ring is divided into segments which are individually interrogated by the measuring electronics in a fast and multiplexed manner. In this way, images are directly generated from acquired signals of electrodes, in a way that visually represents the investigated geometry avoiding the use of some image reconstruction technique. The sensor is fabricated in a flexible printed-circuit board which is flush- mounted inside the pipe wall. A measuring electronics is responsible to detect the capacitance changes in the electrodes. The introduced sensor along with the associated electronics has been tested in static and dynamic two-phase flow, both horizontally and vertically. Direct images were generated in these different situations showing satisfactory results when compared to a reference sensor. Main contribution of this work is the introduction of a new measuring tool which is able to image flow (also containing electrically non-conducting fluids) with no need to apply image reconstruction techniques.